'There is always a scientific explanation' - UMP, . (Penerbit, Percetakan New Straits Times, 2015)
Kuantan: Do ghosts really exist? Going by the number of hits on YouTube for ghostly videos and the number of people who flock cineplexes to watch movies on the supernatural, many, whether or not they believe in ghosts, are interested in all things spooky